Analysis of the contributions of the Science Fair in the development of scientific education, in social and environmental aspects, in the strengthening of pedagogical practice in school spaces in the Municipality of Alto Alegre, State of Roraima (RR), Brazil (Research, Society and Development, 2025)
This research aimed to analyze the contributions of science fairs to the development of science education, social and environmental aspects, the strengthening of pedagogical practices in schools in the municipality of Alto Alegre, RR, and their influence on the formation of scientifically literate individuals. The methodology used was qualitative and quantitative research and the hermeneutic method. The data collection instrument consisted of questionnaires administered to teachers (20), academics (20), and students (40) who participated and registered in the science fair over the last three years. The questionnaires assessed their experiences and participation in these events and how they contributed to their growth and development as individuals. This study reflects on the importance of education with quality and innovation, as recommended by the SDGs (Sustainable Development Goals). As a result, given the research, it is essential that educators, students, and administrators recognize the importance of actively developing science fairs, with a proactive role, understanding that participation is not limited to being present, but involves genuine commitment, the search for problem-solving, the development of critical thinking, and the creation of science, learning, and the exchange of ideas. Fairs represent a privileged space for educational practice, where theories learned in the classroom are realized in the living, breathing reality of students' experiences.